Advanced Yolk-Shell Nanoparticles as Nanoreactors for Catalysis - Wang, Meiwen (Curtin University, 2017)
This thesis presents a series of works on the design, synthesis and application of yolk-shell structured nanoparticles. Several facile and efficient fabrication methods were developed to precisely control the size and shape of yolk-shell nanoparticles and they were evaluated in catalytic performances for energy related applications. Furthermore, the materials and architectures were finely tuned for improving the morphology and also the performance as yolk-shell nanoreactors. This thesis makes contributions to materials science and catalysis.